Combining biosafety expert’s evaluation and workers’ perception regarding the Biological Risks in Biomedical laboratories of Public Hospitals in Athens, Greece - Dionysios Vourtsis; Efstathia Papageorgiou; Anastasios Kriebardis; George Albert Karikas; Gijsbert van Willigen; Kostas Kotrokois; Georgios Dounias; Petros Karkalousos (European Scientific Journal, ESJ, 2024)
Objectives: The aim of the present study was by combining an expert’s evaluation and laboratory workers’ perception, to review the biological risks in biomedical laboratories of public hospitals in Athens, Greece. It was also to evaluate how they are managing the biological materials, the level of safety awareness and training of the personnel, and to propose mitigation measures according to the existing risks, based on the local legislation and the international Biosafety guidelines. Materials and Methods: A total of 36 biosafety level-2 (BSL2) biomedical laboratories in 20 public hospitals were assessed for their biosafety containment specifics and compliance with biosafety practices. The study was designed as a cross-sectional study, with a checklist and a detailed health and safety (H&S) questionnaire, focused on biosafety and biorisk management. An expert biosafety officer observed and filled in a checklist for each biomedical laboratory (n=36) of the 20 hospitals. Laboratory staff (medical laboratory doctors, medical laboratory technologists, laboratory assistants, biologists and biochemists; n = 415) filled in a specific to biosafety H&S questionnaire in each of these laboratories. Results: Both the results from the checklists and the questionnaires showed that in a significant percentage of laboratories there are the following deficiencies: restricted access and signage at the entrance, autoclaves in the laboratory area, ability to use the washbasins hands-free, biorisk management system, written risk assessments, biosafety manuals, standard operating procedures (SOPs), assigned biosafety officers, protocols  about the use of Personal Protective Equipment (PPE), insufficient biosafety training programs, accidents reporting, eyewash emergency shower system, first aid kits and emergency telephone numbers. On the positive site laboratory procedures are separated from management, sanitary and rest areas, laboratory surfaces and floors are easy to clean and disinfect, good laboratory Practices followed for all procedures, waste management is in compliance with the current Greek legislation and there are sufficient PPE available. Conclusion: In the laboratories studied there are significant shortcomings in containment and administrative controls, in the application of Greek and EU biosafety legislation, and in the proper management of biological agents and materials in general. This emphasizes the importance of closing key gaps in biosafety and emergency preparedness, in the biomedical laboratories. Using the results of this study, actions should be developed, applied and enforced, in compliance with the local and European legislation and guidelines. This could enhance the safety of these facilities, and the laboratory professionals, the community and the environment could be better protected from possible harmful biological agents and the possibility of Laboratory acquired infections (LAIs). This study also demonstrated the value of the laboratory workers participation in the risk evaluation, despite their propensity to over or under-estimate the risk level of the possible hazards. That fact should be considered in future studies when enhancing hospital staff.